Ag/NiO nanocomposites derived from alpha-nickel hydroxide for the detection of microbial volatile organic compounds - Vioto, Gabriel Camilo Negrini [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Microorganisms are widely studied due to the risks they can cause in human activities. It can damage the economy and health fields, causing infectious diseases or even the deterioration of food. Thus, there is a need for the control and identification of these organisms. An essential characteristic of microorganisms, in general, is that they produce specific profiles of microbial volatile organic compounds (mVOC) in their cellular metabolism, which can be correlated with infectious diseases or even particular microorganisms. In this work, α-nickel hydroxide (α-Ni(OH)2) and silver (Ag) were used as a precursor of nickel oxide (NiO) and for decorating NiO with different amounts of % mass, respectively. They aim to obtain materials (NiO and Ag/NiO) with pores and silver in their structures. The modifications can guarantee better performance in applying the material both as a sensor for mVOCs and VOCs, through sensitization reactions, caused by the presence of Ag. For selectivity of the samples, acetone, ethanol, 2-butanone, 3-methyl-1-butanol, 2-nonanone, and m-xylene were used; a better selectivity was obtained for 3-methyl-1-butanol, a mVOC. In addition, sensitivity tests were performed, using different concentrations of 3-methyl-1-butanol in a range of 2 to 200 ppm and a test to obtain the optimum operating temperature of the materials.

Os micro-organismos são amplamente estudados devido aos riscos que podem ocasionar nas atividades humanas. Podendo causar danos desde a área da saúde até a área econômica, ocasionando doenças infecciosas ou mesmo a deterioração de alimentos. Dessa forma, surge a necessidade do controle e identificação destes organismos. Uma importante característica dos micro-organismos em geral é que estes produzem perfis específicos de compostos orgânicos voláteis (mCOVs) em seu metabolismo celular, perfis estes que podem ser correlacionados com doenças infecciosas ou mesmo micro-organismos específicos. Neste trabalho, foi utilizado de αhidróxido de níquel, como precursor para síntese de óxido de níquel (NiO) e do NiO decorado com diferentes quantidades de % massa de Ag, respectivamente. Visando a obtenção de materiais (NiO e Ag/NiO) com morfologias semelhante a pétalas e com prata em suas estruturas. Modificações estas que podem promover um melhor desempenho na aplicação do material tanto como sensor de mCOVs quanto de COVs, possivelmente obtida por reações de sensibilização, ocasionadas pela presença de Ag. Em seguida, foram realizados testes de seletividade para as amostras. Para a seletividade foram utilizados, acetona, etanol, 2-butanona, 3-metil-1-butanol, 2-nonanona e mxileno, onde foi obtido uma melhor seletividade para o 3-metil-1butanol, um exemplo de mCOV. Além disso, foram realizados testes de sensibilidade, utilizando diferentes concentrações de 3-metil-1-butanol em uma faixa de 2 a 200 ppm. Também foram realziados testes para a obtenção da temperatura de trabalho das amostras.
Nanocompósitos de Ag/NiO derivados de α-hidróxido de níquel para detecção de compostos orgânicos voláteis microbianos
Keywords: Microbial volatile organic compounds; α-Nickel hydroxide; Nickel oxide; Silver decorating; Nanocomposite; Compostos orgânicos voláteis microbianos; α-Hidróxido de níquel; Óxido de níquel; NiO decorado com Ag; Nanocompósitos